Efficient frequency conversion based on local optimization theory. (18th November 2015) - Xu, Lei; Chen, Changshui; Zhao, Xiangyang; Liu, Tuo; Hu, Hui
Abstract: We discuss theoretically a robustness of the difference frequency conversion method and demonstrate it by numerical simulation. This technique, borrowed from an analogous scheme of robust population transfer in atomic physics and nuclear magnetic resonance called 'local optimization', can keep the intermediate frequency fixed and make the counterintuitive ordering emerge automatically. Here we show an efficient frequency conversion in two-process three wave mixing (TWM). And because the local optimization method is a well-defined, automated computational procedure, we think it would be very useful in the efficient conversion of complicated multi-process TWM, which is a difficult subject in STIRAP.